THE IMPORTANCE OF INTERACTIVE METHODS AND TECHNOLOGIES IN IMPROVING EDUCATIONAL EFFICIENCY - М. Аkhmedbekova (European Journal of Interdisciplinary Research and Development, 2023)
The effective organization of the educational process, the effective use of interactive methods and information opportunities in training, of course, makes it possible to increase the quality of Education. To do this, the explanation of theoretical knowledge in the course of the lesson on the basis of various interesting methods sets the stage for increasing student activity. The teacher should use such a method in the lesson so that he does not take too much time in the lesson, so that in use both the teacher and the student do not have difficulties.